2013
DOI: 10.1016/j.jpeds.2013.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Costs of Hospital Admissions in First Year of Life: A Population-Based Study

Abstract: Objective: Identify health care utilization and associated costs of infants with and without severe neonatal morbidity in the first year of life.Methods: Data from the Perinatal Data Collection for all 601,455 live born infants born in NSW, Australia, 2001Australia, -2007 were linked to hospital admission data. Logistic regression models were used to investigate the association between severe neonatal morbidity and readmission to hospital once, and more than once in the first year; and average costs were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 34 publications
(40 reference statements)
3
48
0
Order By: Relevance
“…In Australia, each additional completed week of gestation was found to reduce mean cost during the first year of life by 10% and 27% for infants with and without severe neonatal morbidity, respectively. 24 Prevention of the synergistic combination of birth defects and preterm birth may yield higher cost savings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Australia, each additional completed week of gestation was found to reduce mean cost during the first year of life by 10% and 27% for infants with and without severe neonatal morbidity, respectively. 24 Prevention of the synergistic combination of birth defects and preterm birth may yield higher cost savings.…”
Section: Discussionmentioning
confidence: 99%
“…Among infants who are relatively healthy, the association of preterm birth with increased expenditures is lower than it is among those with severe neonatal morbidity. 24 The implication is that the estimates of per-child expenditures associated with preterm birth (especially late preterm birth) may be substantially overstated by using stand-alone administrative databases. On the other hand, the incomplete sensitivity of the ICD-9-CM codes for ascertaining preterm births does not bias aggregate estimates of expenditures; rather, the aggregate estimates are conservative because they do not include any incremental health care cost for late preterm infants who are not coded as preterm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Infants born at 37 to 38 weeks' gestation have been shown to have an increased risk for readmission for jaundice previously 10 ; however, the impact of early discharge on these infants has not been investigated. An increasing amount of research about early term infants has shown these infants have more neonatal morbidity, 20 poorer long-term general health, 21 higher health service use and costs, 13 and poorer educational results 22 than infants born at 39 to 41 weeks' gestation.…”
Section: Figurementioning
confidence: 99%
“…13 The aims of this study are to (1) examine the association between early discharge from hospital after birth, week of gestational age, and readmission to hospital for jaundice among term infants; and (2) investigate the perinatal risk factors for readmission to hospital for jaundice among infants discharged early.…”
mentioning
confidence: 99%